Prevention of osteoradionecrosis of the jaws with the association of pentoxifylline and tocopherol in the dentistry service in an oncology reference hospital (Research, Society and Development, 2022)
To analyze the use of the PENTO protocol (pentoxifylline and tocopherol) in a preventive way for ORN in patients undergoing post-RT extraction in the head and neck region at the Dentistry service of the Hospital de Câncer de Pernambuco. A total of 74 tooth extractions were performed in patients who underwent RT in the head and neck region. Patients used PENTO (pentoxifylline 400mg + tocopherol 400mg) 3 times a day starting 15 days before the surgical procedure until the mucosal covering of the operated alveolus. Antibiotic therapy (amoxicillin 500mg or clindamycin 300mg for allergic patients) was performed, starting 48 hours before the procedure and lasting up to ten days after the procedure. All tooth extractions were performed by the same surgeon and suture removal was performed after 7 days. Assessments were performed regarding the presenc of pain, of infection, bone exposure, use of analgesics, mucosal covering and adverse effects of medications every 7 days for 28 days. 61% of the patients had no painful symptoms on D7 and 74% did not use analgesics in the same period. Presence of infection was observed in 2% of participants and total mucosal coverage was observed on D14 in 86% of cases. There was no record of alveolitis or ORN. Nausea and dizziness, 14 and 12% respectively, were the most common adverse effects. Based on the results obtained, we can suggest that the association of PENTO may play an important role in the prevention of ORN, in addition to reducing the need for analgesics.